Environmental Stress Testing of Wafer-Level Al-Al Thermocompression Bonds: Strength and Hermeticity. (1st May 2015) - Malik, N.; Poppe, E.; Schjølberg-Henriksen, K.; Taklo, M. M. V.; Finstad, T. G.
Abstract : Hermeticity, reliability and strength of Al-Al thermocompression bonds realized by applying different bonding parameters have been investigated. Laminates of diameter 150 mm were realized by bonding wafers containing membrane structures to wafers with patterned bonding frames. The laminates were bonded applying a bond force of 36 or 60 kN at temperatures ranging from 300 to 400°C for 15, 30 or 60 minutes. The hermetic properties were estimated by membrane deflection measurements with white-light interferometry after bonding. Reliability was tested by exposing the laminates to a steady-state life test, a thermal shock test, and a moisture resistance test. Bond strength was measured by shear test and pull tests. Laminates bonded applying a bond force of 60 kN at temperatures of 350 or 400°C resulted in hermetic bonds. No significant change in membrane deflection was observed after the steady-state life test or the thermal shock test. However, a gross leakage was observed in 1–11% of the dies after exposure to the moisture resistance test. The maximum leakage rate (MLR) estimated from membrane deflection measurements was below 10 −11 mbar·l·s −1 for all laminates. The measured average bond strength of dies from selected laminates ranged from 28 to 190 MPa.